Dual Targeting of the Warburg Effect with a Glucose‐Conjugated Lactate Dehydrogenase Inhibitor. Issue 17 (31st October 2013) - Calvaresi, Emilia C.; Granchi, Carlotta; Tuccinardi, Tiziano; Di Bussolo, Valeria; Huigens, Robert W.; Lee, Hyang Yeon; Palchaudhuri, Rahul; Macchia, Marco; Martinelli, Adriano; Minutolo, Filippo; Hergenrother, Paul J.
<x xml:space="preserve">Abstract</x> Effective glucose diet: We report the development and activity of glucose‐conjugated LDH‐A inhibitors designed for dual targeting of the Warburg effect (elevated glucose uptake and glycolysis) in cancer cells. Glycoconjugation could be applied to inhibitors of many enzymes involved in glycolysis or tumor metabolism.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>